Effects of verbatim repetition of the headline message on the proceed button on click-through rates in online retail - Kutzner, Florian; Ermark, Florian K. G.; Fornoff, Julian; Wänke, Michaela (Frontiers in Psychology, 2024)
For online retailers, increasing click-through rates and reducing dropout rates are critical to success. In this study, we examine the effect of verbatim repetition of the website's headline message on the proceed button, based on research on processing fluency. In our field study involving 956 online platform visitors, we found that verbatim repetitions of the header message on the proceed button resulted in an increase in the conversion rate by more than 10 percentage points compared to gist repetitions and new messages. Our findings highlight the importance of simple verbatim features and demonstrate the successful application of processing fluency research to impact consumer behavior.